The same bright stars : a novel - Joella, Ethan (Scribner, 2024)
"Three generations of Schmidts have run their family's beachfront restaurant and Jack has been at the helm since the death of his father. Jack puts the demands of the restaurant above all else, with a string of failed relationships, no hobbies, and no days off as proof of his commitment to the place. He can't remember the last time he sat on the beach, or even enjoyed a moment to himself. Meanwhile, the DelDine group has been gradually snapping up beloved eateries along this stretch of coast and are pursuing Jack with a very generous offer to take Schmidt's off his hands. Jack craves companionship and maybe even a family. He wonders if closing the door on the restaurant might open a new window for him. But who would he be without Schmidt's, and can he trust DelDine's claims that they will continue to employ his staff and honor his family's legacy? When he receives startling news from the past, Jack begins to reshape his life and forge unexpected new friendships. But will he really let go of the very things that have defined him?"--